Antibiotic resistance pattern and its correlation to the presence of tdh gene and CRISPR-Cas system in Vibrio parahaemolyticus strains isolated from seafood - Baliga, Pallavi; Shekar, Malathi; Ahamed, Shaik Tahur; Venugopal, M. N. (Indian Journal of Fisheries, 2019)
Vibrio parahaemolyticus is a pathogen native to the aquatic environment. In this study, 46 environmental V. parahaemolyticus isolates were subjected to a correlational analysis to find the association between their antimicrobial susceptibility pattern, prevalence of CRISPR-Cas system and thermostable direct hemolysin (tdh) gene. Antibiotic resistance profiling against eleven antibiotics revealed the isolates to be multidrug resistant. Isolates exhibited highest resistance to vancomycin (97.8%) followed by ampicillin (91.3%), cefotaxime (69.6%), ceftazidime/clavulanic acid (54.4%), ceftazidime (45.7%) and gentamicin (39.1%). CRISPR loci and tdh gene were detected in 47.83 and 58.7% of strains respectively. No significant correlation was observed between antibiotic resistance to presence of CRISPR, except in the case of gentamicin wherein, a negative correlation was seen (r=-0.272, p